Legitimation, Self-Censorship, and Fatherhood: Garcilaso Inca and Diego de Vargas. - CÁRDENAS BUNSEN, JOSÉ (Revista Hispánica Moderna (0034-9593), 2021)
The article discusses mestizo chronicler Garcilaso de la Vega's self-imposed censorship on his fatherhood. It demonstrates that his authorial silence reveals a crucial intersection between his life and writings that informs his views on education and is part of an effort to promote the legitimation of his own son through the textual erasure of their attachment; and also mentions details of Diego de Vargas's baptism and ordination, and links his biographical narrative, submitted for his application to orders, with Garcilaso's social discretion regarding his paternal ties and with his authorial self-censorship that avoids explicit references to his fatherhood.